O ensino de língua inglesa para o aluno surdo no contexto da educação inclusiva - Athená Menezes Ferreira (2024)
This study focuses on teaching and learning the English language, especially within the context of Inclusive Education. With the increasing inclusion of students with multiple disabilities, especially deaf ones, there is a demand for pedagogical approaches that optimize their learning experience. English, which is a crucial tool in the globalized scenario, is a vital skill for everyone, including the deaf community. It is essential to create inclusive learning environments that celebrate the richness of different languages and cultures. By integrating local languages and cultural elements into English classrooms, we can foster a sense of pride and belonging among students, while also promoting intercultural and respect understanding. The term "additional language" is introduced to represent this complex learning. Deaf people not only have a unique language, but also a distinct culture, and it is imperative that pedagogical strategies recognize and value this uniqueness. The research methodology is qualitative, with the central problem being understanding how the current educational system assists deaf people in acquiring the English language in an inclusive environment. To this end, English classes were observed in an inclusive state public school with two deaf students enrolled. The data collection involved observation, field notes and questionnaires. The results of the analysis highlight the relevance of the sign language in the teaching process for deaf students. The data also reveal that the methodology used by the teacher only matches the hearing student, as the oral modality is the main means of communication. The deaf student is instructed to learn English through differentiated teaching material with superficial explanations given in Portuguese by the teacher and interpreted into Libras by the interpreter. Inclusion in the context of learning English is identified as a challenge, and may even prevent deaf students from learning. Therefore, this research aims to analyses the classroom practices to offer, in the future, more effective educational solutions for deaf people.